2004
DOI: 10.1007/s00421-004-1063-z
|View full text |Cite
|
Sign up to set email alerts
|

Passive hyperthermia reduces voluntary activation and isometric force production

Abstract: It has been suggested that a critically high body core temperature may impair central neuromuscular activation and cause fatigue. We investigated the effects of passive hyperthermia on maximal isometric force production (MVC) and voluntary activation (VA) to determine the relative roles of skin (T(sk)) and body core temperature ( T(c)) on these factors. Twenty-two males [VO(2max)=64.2 (8.9) ml x kg(-1) min(-1), body fat=8.2 (3.9)%] were seated in a knee-extension myograph, then passively heated from 37.4 to 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
212
4
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(250 citation statements)
references
References 29 publications
27
212
4
7
Order By: Relevance
“…In addition, hyperthermia was achieved actively, altering peripheral metabolic characteristics that could further influence peak force. Still, other studies (16,33) have demonstrated progressive decreases in MVC and voluntary activation with increasing core temperatures in the range of the present study. It is possible that mechanisms of task failure for the small hand muscles used in the present study differ from those of the knee extensors and plantar flexors of those studies (7,16).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In addition, hyperthermia was achieved actively, altering peripheral metabolic characteristics that could further influence peak force. Still, other studies (16,33) have demonstrated progressive decreases in MVC and voluntary activation with increasing core temperatures in the range of the present study. It is possible that mechanisms of task failure for the small hand muscles used in the present study differ from those of the knee extensors and plantar flexors of those studies (7,16).…”
Section: Discussioncontrasting
confidence: 51%
“…passive hyperthermia; recruitment curve; transcranial magnetic stimulation HIGH INTERNAL TEMPERATURE, ranging from 38.6 to 40.3°C, is associated with voluntary exhaustion during aerobic exercise, despite variations in baseline core temperature, heat storage rates, and final skin temperature (4, 10). Similarly, hyperthermia has been shown to produce motor fatigue, evidenced by decreased voluntary activation during sustained maximal voluntary contractions (MVC) (16,34). Cardiovascular strain during thermal stress contributes to the development of fatigue; however, evidence also suggests that hyperthermia alters central nervous system (CNS) functions, resulting in alterations in voluntary activation of muscle, as well as changes in perception of effort (18,24,33).…”
mentioning
confidence: 99%
“…Recent studies using passively induced hyperthermia have demonstrated that heat-related impairment of force development is attributable to both central and peripheral effects (35,54). Thus high body temperature itself can impair exercise tolerance independently of its effects in elevating cardiovascular, metabolic, and neuroendocrine strain.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism presupposes that approaching or achieving the higher brain and core temperature is a symptom of exhaustion development to keep the individual being knocked down. Morrison, Sleivert, and Cheung (2004) has shown a progressive central disruption associated with increased temperature. Therefore, it seems that during exercise under increased thermal pressure, high body temperature may directly or indirectly affect endurance performance.…”
Section: Temperature and Central Fatiguementioning
confidence: 99%